THE EFFECT OF USING QUESTION STRATEGY ON STUDENTS’ READING COMPREHENSION - Kresna Ningsih Manik; Dolli Rotua Sinaga (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
This research was aimed to find out the effect of using question strategy on students’ reading comprehension in Prima Indonesia University, Medan, academic year 2019/2020. In this research, the subjects were 2 classes of second semester with 30 students each class. This research was a quasi experimental with two groups pretest and post test design. The procedures of collecting data are divided into three parts, they are pretest, treatment and post-test. The  data can be calculated by scoring two groups paper are count answer get 1 point from 20 questions. The hypothesis is proved the value of t-observed is higher than t-table they are ( 3.21>1.671) at the level of significance alpha 0.05 and the degree of freedom (df)= 58. It can be concluded that the students were taught by using question strategy significantly affects on students’ reading comprehension.